2022
DOI: 10.3389/fpubh.2022.877073
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Predictors of Malnutrition Among Indian Adolescents (10–19 Years): Insights From Comprehensive National Nutrition Survey Data

Abstract: Introduction:Malnutrition among adolescents is a persistent problem with a profound impact on different dimensions of health. The objective of this analysis is to assess the burden of malnutrition (Stunting, Thinness, Overweight, and Obesity) and their associated socio-demographic factors among Indian adolescents (10–19 years) from the Comprehensive National Nutritional Survey (CNNS 2016-18) data.MethodsWe used Individual-level data of 35,831 adolescents from the CNNS conducted in 2016–18 for this analysis. CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…This further suggests that China should pay attention to the dissemination of nutritional concepts and balanced development of each region while actively building the countryside and ensuring nutritional needs. The older the age, the lower the prevalence of thinness and overweight and obesity in all subgroups, consistent with related studies ( 6 , 8 , 20 ). Some studies also showed opposite results or little difference among different age categories ( 18 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This further suggests that China should pay attention to the dissemination of nutritional concepts and balanced development of each region while actively building the countryside and ensuring nutritional needs. The older the age, the lower the prevalence of thinness and overweight and obesity in all subgroups, consistent with related studies ( 6 , 8 , 20 ). Some studies also showed opposite results or little difference among different age categories ( 18 ).…”
Section: Discussionsupporting
confidence: 91%
“…Overall the prevalence of thinness was consistent in boys and girls, and the prevalence of overweight and obesity was higher in boys, consistent with previous studies ( 7 , 8 , 20 , 24 , 25 ). However, some studies showed that girls were more likely to be stunted or thin ( 6 , 21 ) and others demonstrated that boys were more likely to be stunted or thin ( 29 , 39 ). It was speculated that these differences may be related to the country and the different regions.…”
Section: Discussionmentioning
confidence: 99%
“…But due to lack of comprehensive and representative data on adolescent nutrition, the scope of earlier studies is a limited to specific region or gender ( 8 , 9 , 13 , 14 ) . Two recent studies on adolescent malnutrition ( 15 ) and anaemia ( 16 ) conducted using CNNS (2016–18) data shows substantial socioeconomic and regional disparities in adolescent malnutrition. However, none of these large-scale studies assessed the roles of dietary diversity and individual-level hygiene practices in adolescent malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐one studies explored differences between rural and urban areas and the majority of them (16 studies) (Bellundagi et al, 2022; Bhargava et al, 2016; Biswas et al, 2017; Chakraborty et al, 2018; Ganie et al, 2017; Goonapienuwala et al, 2022; Harding et al, 2019; Hombaiah et al, 2021; Islam et al, 2020; Khan et al, 2022; Khatri et al, 2021; Mohan et al, 2019; Pandurangi et al, 2022; Prasad et al, 2016; Yadav et al, 2018; Young et al, 2020) found a higher prevalence of overweight and/or obesity in urban areas. Differences in overweight/obesity prevalence for males and females were inconsistent across studies; however, a pooled analysis combining 2416 population‐based measurements found that BMI was higher among girls compared to boys in South Asia (NCD Risk Factor Collaboration (NCD‐RisC), 2017).…”
Section: Resultsmentioning
confidence: 99%